Pebbles, rocks, and boulders: The implementation of a school-based social engagement intervention for children with autism. (November 2017) - Locke, Jill; Wolk, Courtney Benjamin; Harker, Colleen; Olsen, Anne; Shingledecker, Travis; Barg, Frances; Mandell, David; Beidas, Rinad
Few evidence-based practices, defined as the use of empirically supported research and clinical expertise for children with autism, have been successfully implemented and sustained in schools. This study examined the perspectives of school personnel ( n  = 39) on implementing a social engagement intervention for children with autism. Semi-structured interviews, informed by the Domitrovich et al. (2008) framework, were conducted. Participants were asked about (1) school factors that affect the general implementation of evidence-based practices, (2) their specific experiences implementing the social engagement intervention, and (3) barriers to and facilitators of implementing the social engagement intervention. Data were analyzed using an integrated approach. General (e.g. implementation process, leadership, support, and staff) and intervention-specific (e.g. staff, barriers, and facilitators) implementation themes were identified. These findings suggest that a variety of factors should be considered when implementing evidence-based practices in schools and that implementing social engagement interventions for children with autism may require additional specific support for implementation.